EVALUATION OF ANTINOCICEPTIVE AND ANTIEXUDATIVE EFFECTS OF A COMPLEX HERBAL PREPARATION IN THE THERAPY OF SOMATIC PAIN AND INFLAMMATION OF DIFFERENT ORIGIN - Nefodov, O.O.; Eberle, L.V.; Tsisak, A.O.; Gritsuk, O.I.; Aleksandrova, O.I.; Guzenko, O.M.; Shkodovska, A.M.I.; Burega, I.Y. (World of Medicine and Biology, 2023)
Experimental studies of the antinociceptive effect of the complex herbal preparation on models of somatic pain induced by thermal and chemical stimuli were performed, and the antiexudative impact of the drug was established on models of inflammation of various genesis. The experimental sample of the herbal preparation is presented in the form of an ointment for transdermal administration and contains a complex of plant extracts: Juglans nigra L., Acorus calamus L., Styphnolobium japonicum L. and Zingiber officinale L. The study's results indicate the effectiveness of the drug in treating somatic pain with skin damage and in deep somatic manifestations of pain reactions. The activity of the herbal preparation was not inferior to that of the comparison drug. In the trypsin and zymosan models of edema, the complex herbal preparation has pronounced anti-inflammatory activity when administered transdermally. It suppresses cyclooxygenase and lipoxygenase activity, making it a promising object for further pharmacological study and introduction into medical practice as an alternative means of treating somatic pain and inflammatory processes.
Keywords: herbal preparation; antinociceptive and antiexudative action; inflammation; somatic pain